Per- and poly-fluoroalkyl substances (PFAS) effects on lung health: a perspective on the current literature and future recommendations - Solan, Megan E.; Park, Jin-Ah (Frontiers in Toxicology, 2024)
Per- and poly-fluoroalkyl substances (PFAS) are a broad class of synthetic compounds widely used in commercial applications. The persistent nature of PFAS in the environment has earned them the epithet “forever chemicals.” Concerns arise from widespread exposure to PFAS from occupational, household, and environmental sources. This widespread use of PFAS is particularly concerning, as emerging epidemiological evidence highlights their adverse effects on lung health. Such adverse impacts include impaired fetal lung development, reduced immune function in children, and potential links to lung cancer. Both in vivo and in vitro studies illuminate potential mechanisms underlying such adverse health outcomes subsequent to PFAS inhalation exposure, which may include immunomodulation, oxidative stress, and disruptions to epithelial barriers. However, evidence-based information focusing on the mechanisms of PFAS-mediated lung injury is lacking. Additionally, the discrepancies between data collected from animal and epidemiological studies highlight the need for improved approaches to better understand the toxicity results of PFAS exposure. To address these gaps, we recommend leveraging route-to-route extrapolation for risk assessment, prioritizing research on understudied PFAS, and adopting physiologically relevant, high-throughput approaches. These strategies are aimed at enhancing our understanding of PFAS inhalation effects, aiding in more informed risk management decisions. In this review, we summarize the current literature on PFAS exposure, emphasizing its adverse effects on lung health, particularly through inhalation. We then discuss the current knowledge on mechanisms underlying tissue- and cellular-level adverse outcomes caused by PFAS.